2006
DOI: 10.1177/1099800405285258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endotracheal Tube Suctioning on Arterial Oxygen Tension and Heart Rate Variability

Abstract: The purpose of this study was to examine the autonomic mechanisms underlying changes in heart rate (HR) and systolic blood pressure (SBP) responses to endotracheal tube (ETT) suctioning and to compare the open versus closed methods of ETT suctioning on these measures and on arterial oxygen tension. Eighteen orally intubated participants, 33 to 82 years of age (M = 60 years), were randomized for the order of suctioning method. Arterial oxygen tension (PaO2) was measured before suctioning and 30 s and 5 min foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
56
4
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 30 publications
6
56
4
6
Order By: Relevance
“…An increase in HR during ETT suction, of similar magnitude to that in our study, has previously been reported in the preterm neonate (16). The cause of the increase in HR during ETT suction is postulated to be an autonomic response whereby a reduction in arterial oxygen tension is detected by the medulla, resulting in increased sympathetic efferent activity (16).…”
Section: Chorioamnionitis Alters Hemodynamicssupporting
confidence: 66%
See 2 more Smart Citations
“…An increase in HR during ETT suction, of similar magnitude to that in our study, has previously been reported in the preterm neonate (16). The cause of the increase in HR during ETT suction is postulated to be an autonomic response whereby a reduction in arterial oxygen tension is detected by the medulla, resulting in increased sympathetic efferent activity (16).…”
Section: Chorioamnionitis Alters Hemodynamicssupporting
confidence: 66%
“…Endotracheal tube (ETT) suction is one of the most common interventions performed during respiratory support of preterm infants and is known to alter lung mechanics and systemic hemodynamics (3,(16)(17)(18)(19)(20). However, to our knowledge, the impact of prior exposure to intrauterine inflammation on these consequences is unknown.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, changes in heart rate were significant in one study (9), which was in contrary to findings of the other investigations (10,11). In addition, changes in arterial oxygen saturation between two procedures were significant in two studies (11,12), while they were not significant in a study reported by Fernandez et al (10).…”
Section: Introductioncontrasting
confidence: 55%
“…In recent years, several studies have compared the effects of the two suctioning methods (9)(10)(11)(12)(13)(14); however, the results are contradictory. For example, changes in heart rate were significant in one study (9), which was in contrary to findings of the other investigations (10,11).…”
Section: Introductionmentioning
confidence: 99%